Beryllium isotope variations recorded in the Adélie Basin, East Antarctica reflect Holocene changes in ice dynamics, productivity, and scavenging efficiency - Behrens, Bethany C.; Yokoyama, Yusuke; Miyairi, Yosuke; Sproson, Adam D.; Yamane, Masako; Jimenez-espejo, Francisco J.; Mckay, Robert M.; Johnson, Katelyn M.; Escutia, Carlota; Dunbar, Robert B. (Quaternary Science Advances, 2022)
The Adélie Basin is a relatively small (∼1600 km2), semi-enclosed continental shelf bathymetric depression located adjacent to the Wilkes Subglacial Basin, a basin underlying a sector of the East Antarctic Ice Sheet that contains ∼3–4 meters sea level equivalent of ice. Located within the Adélie Basin is a ∼184 m thick laminated sediment deposit, the Adélie Drift, ideal for examining regional changes in ice sheet and ocean dynamics. Here, we examine the ratio of reactive beryllium-10 to reactive beryllium-9 ((10Be/9Be)reac) in a marine sediment core obtained from the Adélie Drift to assess these changes during the Holocene epoch (11.7 ka BP to present). The (10Be/9Be)reac record provides insight into changes in freshwater input, primary productivity, and scavenging efficiency, while removing the influence of particle size on 10Be concentration. During the early Holocene, (10Be/9Be)reac ratios indicate increased meltwater discharge from ca. 11.7 to 10 ka BP, as grounded ice retreated from the Adélie Basin and adjacent bathymetric highs. After ∼10 ka BP, beryllium isotopes are influenced by scavenging efficiency and dilution controlled by ocean currents and accumulation rate, operating alongside meltwater input, suggesting there are additional factors to consider when using (10Be/9Be)reac as a proxy for ice shelf cover and glacial dynamics.